Annex VI to the Protocol of Environmental Protection to the Antarctic Treaty : message from the President of the United States transmitting Annex VI on liability arising from environmental emergencies to the Protocol on Environmental Protection to the Antarctic Treaty (Annex VI), adopted on June 14, 2005 - United States. President (2009- : Obama); Clinton, Hillary Rodham (United States. Government Printing Office., 2009)
This amendment to the Antarctic Treaty deals with preventing and managing environmental emergencies in the Antarctica Treaty area.